ARC: a framework for access, reciprocity and conduct in psychedelic therapies - Spriggs, Meg J.; Murphy-Beiner, Ashleigh; Murphy, Roberta; Bornemann, Julia; Thurgur, Hannah; Schlag, Anne K. (Frontiers in Psychology, 2023)
The field of Psychedelic Assisted Therapy (PAT) is growing at an unprecedented pace. The immense pressure that this places on those operating in this space has already begun to raise important questions about risk and responsibility. It is imperative that the development of a safe and equitable infrastructure for psychedelic care is prioritised, and we utilise this unique opportunity to shape a new chapter in bio-psycho-socio-spiritual approaches to healing and wellbeing. Here we present ARC; a framework for a culturally informed ethical infrastructure for Access, Reciprocity and Conduct in psychedelic therapies. The three parallel yet interdependent pillars of ARC provide the bedrock for an infrastructure that respects the cultural roots of these medicines, protects the safety of those delivering and receiving these treatments, and prioritizes and empowers the communities most in need. In the development of ARC, we are taking a novel dual-phase co-design approach. The first phase involves co-development with relevant stakeholders from research, industry, therapeutic, community, and indigenous contexts. A second phase will draw upon the collective wisdom of the wider psychedelic community. By presenting ARC at this early stage, we hope to inspire the open dialogue and collaboration upon which the process of co-design depends, and that together, we can ensure a safe, and equitable future for PAT.